GE_GERICHTE P/13397/2011 vom 10. März 2014 - GE Cour de justice (2014)
INFRACTIONS CONTRE L'INTÉGRITÉ SEXUELLE ; CONTRAINTE SEXUELLE ; VIOL ; INDEMNITÉ(EN GÉNÉRAL) | CP.189.1; CP.189.3; CP.190.1; CP.190.3